PENERAPAN KONSELING BEHAVIORISTIK TEKNIK KONTRAK PERILAKU UNTUK MENGATASI KECANDUAN SOSIAL MEDIA INSTAGRAM PADA SISWA SMPN 3 JUWANA - Eko Puspito Hartomo; Indah Lestari; Santoso Santoso (Jurnal Muria Research Guidance and Counseling (MRGC), 2022)
The research objectives to be achieved are as follows: 1. To find out the factors that cause addiction to Instagram social media and 2. To describe the application of behavioristic counseling of behavioral contracting techniques to overcome addiction to Instagram social media in SMPN 3 Juwana students. The type of research in the research chosen by the researcher is qualitative in the form of a case study. There were two subjects in the study, namely NS and DA students who were addicted to social media Instagram in class VIII of SMPN 3 Juwana. Analysis of the data used is the analysis of the bacon induction system where the researcher will get concrete and complete data to get a conclusion. From the results of the key research, the researchers concluded that behavioristic counseling behavioral techniques were able to overcome addiction to Instagram social media in students of SMPN 3 Juwana.